Life Cycle Assessments of different electricity production scenarios in France with a variable proportion of nuclear energy. Issue 6 (3rd May 2023) - Cassoret, Bertrand; Balavoine, François; Roger, Daniel
ABSTRACT: The environmental impacts of four French scenarios of electricity production systems are compared. They propose a variable part of nuclear which is essentially replaced by wind and solar energy. The paper proposes a comparison of these scenarios based on a Life Cycle Assessments. The systems with a large part of intermittent wind and solar sources need a higher installed power. In addition, for the same installed power, renewable energies require more building materials than nuclear ones. Therefore, the environmental impacts of infrastructures increase with the part of renewable energy. During the use phase, the environmental impacts of fossil fuels, especially coal, are significant. Consequently, the best systems must use the least fossil fuels and need the lower installed power. Finally, if we exclude the risk of nuclear disaster and if we consider that nuclear wastes are well managed, the electricity production systems that achieve the lowest environmental impacts, with the same availability for the electricity to end users, are those that have a large part of nuclear power.